The Association Between Etiologies and Mortality in Acute Respiratory Distress Syndrome: A Multicenter Observational Cohort Study - Wang, Yan; Zhang, Linlin; Xi, Xiuming; Zhou, Jian-Xin; , The China Critical Care Sepsis Trial (CCCST) Workgroup; Du, Bin; Weng, Li; Li, Tong; Duan, Meili; Li, Wenxiong; Sun, Bing; Zhou, Jianxin; et al. (Frontiers in Medicine, 2021)
Background Lung-protective ventilation has been beneficial in acute respiratory distress syndrome (ARDS) patients. As a vital part of Lung-protective ventilation, PEEP can enhance oxygenation. However, randomized clinical trials of different PEEP strategies seem to show no advantages in clinical outcomes in ARDS patients. A potential reason is that diverse etiologies and phenotypes in ARDS patients may account for different PEEP responses, resulting in variations in mortality. We consider hospital mortality associated with a more specific classification of ARDS, such as sepsis-induced or not, and pulmonary or extrapulmonary one. Our study aimed to compare clinical outcomes in various ARDS patients by etiologies using the China Critical Care Sepsis Trial database. This was a retrospective analysis of a prospective cohort of 2,138 ARDS patients in that database. According to ARDS induced by sepsis or not and medical history, patients were stratified into four groups. Differences among groups were assessed mortality, ventilation-free days, and other clinical features. Results A total of 2,138 ARDS patients were identified in the database, including 647 patients with sepsis-induced pulmonary ARDS (30.3%), 396 with sepsis-induced extrapulmonary ARDS (18.5%), 536 with non-sepsis pulmonary ARDS patients (25.1%), and 559 with non-sepsis pulmonary ARDS (26.1%). The pulmonary ARDS group had high mortality compared with the extrapulmonary group (45.9% vs. 23.0%, p < 0.01), longer ICU and hospital stays (9 vs. 6 days, p < 0.01, 20 vs. 18 days, p = 0.01, respectively), and fewer ventilation-free days (5 vs. 9 days) in the presence of sepsis. However, the mortality in ARDS without sepsis, that result was inverted compared with extrapulmonary ARDS (pulmonary 23.5% vs. extrapulmonary 29.2%, p = 0.04). After adjusting for the APACHE II and SOFA scores and other clinical features, the sepsis-induced pulmonary condition was still a risk factor for death in ARDS patients (HR 0.66, 95% CI, 0.54–0.82, p < 0.01, compared with sepsis-induced extrapulmonary ARDS and other sub-phenotypes). Conclusions In the presence of sepsis, mortality in pulmonary ARDS is higher compared with extrapulmonary ARDS; however, mortality is inverted in ARDS without sepsis. Sepsis-induced pulmonary ARDS should attract more attention from ICU physicians and be cautiously treated.